Amplitude Modulation Mode of Scanning Ion Conductance Microscopy. (August 2015) - Li, Peng; Liu, Lianqing; Yang, Yang; Zhou, Lei; Wang, Dong; Wang, Yuechao; Li, Guangyong
Live-cell imaging at the nanoscale resolution is a hot research topic in the field of life sciences for the direct observation of cellular biological activity. Scanning ion conductance microscopy (SICM) is one of the few effective imaging tools for live-cell imaging at the nanoscale resolution. However, there are various problems in existing scanning modes. The hopping and AC modes suffer from low speed, whereas the DC mode is prone to instability because of the DC drift and external electrical interference. In this article, we propose an amplitude modulation (AM) mode of SICM, which employs an AC voltage to enhance the stability and improve the scanning speed. In this AM mode, we introduce a capacitance compensation method to eliminate capacitance effect and use the amplitude of the AC current component to control the tip movement. Experimental results on polydimethylsiloxane samples verify the validity of the AM mode and demonstrate an improved performance of both speed and stability of this new mode.